Noncontact button operation system using hand gestures. (January 2022) - Li, Yujie; Hanaoka, Osamu; Yang, Shuo; Serikawa, Seiichi
Abstract: Recently, many noncontact sensors are intended for facilities that require hygiene to be considered. However, there is a problem in that noncontact sensors could malfunction unintentionally. In addition, there is a demerit in that noncontact sensor is not possible to perform complicated operations with one sensor because it would be limited to the simple operation of turning on when hold hand over it. In this paper, we examine the principle of a noncontact sensor that responds only to the action of waving in front of the sensor as an intentional action and does not malfunction. Additionally, since there are large and small hand waving methods, hand waving alone could be used for multiple signals. Experiments show that the proposed system is to realize not only the states of ON and OFF but also various operations with a single noncontact button.